Business model innovation in strategic alliances: a multi‐layer perspective. (17th April 2020) - Spieth, Patrick; Laudien, Sven M.; Meissner, Svenja
Abstract : Business model innovation (BMI) has recently become a topic of interest for research as well as corporate practice. However, we lack specific insights into actors, drivers, and different forms of BMI as the concept is by now mainly addressed in a very general way. In this paper, we analyze how BMI takes place in strategic alliances with the focus of enhancing the recent knowledge about BMI by developing a concept that links firm‐level BMI with alliance‐driven innovation of business models. Against the background of an in‐depth explorative qualitative study, we shed light on the basic nature business model innovation alliances (BMIA) and their effects on both, alliance level and firm level. We develop a process model of BMIA that is the first model providing a holistic picture of this particular type of BMI. Our findings allow for deep insights into BMI processes in incumbent companies and uncover in detail the importance of boundary spanning activities in this realm. By providing these insights, we pave the ground for a new stream of BMI research that focuses on the in‐depth understanding of the role of collaboration and network effects in recent BMI processes. In addition, we show practical benefits for partners in BMI alliances. These insights may help to overcome the traditional fear of negative effects that is still very often prevalent in companies when it comes to issues of partnering with firm external players in strategic issues.